SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BEASISWA PADA SMA YPI DARUSSALAM CERME MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Ayu Candra Ningtyas; Ningtyas, Ayu Candra; Prasetya, Noven Indra (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2022)
The provision of scholarships to YPI Darussalam High School students was made to lighten the burden of students in paying tuition fees. Technology in the era of globalization is now quite important for people's daily lives, computerization is needed to help facilitate people's daily activities. Based on this, a decision support system is needed. For this reason, the research method used is the sample additive weighting (SAW) method, the SAW method is known as the weighted addition method, for the basic concept in this method is to find the weighted summation of the performance ratings on each alternative in all attributes. It is called by the term that the author has described, because basically the SAW method will operate a weighted addition for all attributes in each alternative. The ultimate goal is that the SAW method can compare alternatives in a more balanced way and produce better calculations.